Imaging of α-Synuclein Aggregates in a Rat Model of Parkinson’s Disease Using Raman Microspectroscopy - Sevgi, Fide; Brauchle, Eva M.; Carvajal Berrio, Daniel A.; Schenke-Layland, Katja; Casadei, Nicolas; Salker, Madhuri S.; Riess, Olaf; Singh, Yogesh (Frontiers in Cell and Developmental Biology, 2021)
A hallmark of Parkinson’s disease (PD) is the formation of Lewy bodies in the brain. Lewy bodies are rich in the aggregated form of misfolded α-Synuclein (α-Syn). The brain from PD patients can only be analysed after post-mortem, therefore, limiting the diagnosis of PD to the manifestation of motor symptoms. In PD patients and animal models phosphorylated α-Syn was detected in the peripheral tissues including the gut, thus, raising the hypothesis that early-stage PD could be diagnosed based on colon tissues biopsies. Non-invasive marker-free technologies represent an ideal method to potentially detect aggregated α-Syn in vivo. Raman micro-spectroscopy has been established for the detection of molecular changes such as alterations of protein structures. Using Raman imaging and micro-spectroscopy, we analysed the olfactory bulb in the brain and the muscularis mucosae of colon tissue sections of a human BAC-SNCA transgenic (TG) rat model. Raman images from TG and WT rats were investigated using spectral, principal component analysis (PCA) and true component analysis (TCA). Spectral components indicated protein aggregates (spheroidal oligomers) in the TG rat brain and in the colon tissues even at a young age but not in WT. In summary, we have demonstrated that Raman imaging is capable of detecting α-Syn aggregates in colon tissues of a PD rat model and making it a promising tool for future use in PD pathology.